Financial life skill training for the PKK Mekar Arum Group RW 16 Bojongsoang, Bandung - Ira Murwenie; Abdul Fatah Hassanudin; Alam Avrianto; Dwirani Fauzi Lestari; Rahmina Puspa (Universitas Muhammadiyah Magelang, 2024)
Strong family economic resilience requires solid financial skills, especially for housewives. This community service program aimed to enhance the financial life skills (FLS) of housewives in the Mekar Arum PKK Group, RW 16 Bojongsoang-Bandung, using a Community-Based Learning (CBL) approach. The program was implemented through workshops and interactive simulation games covering financial literacy, household financial management, business development, capital management, investment risks, and insurance. The impact of the program was analyzed using a paired t-test to measure differences in participants' understanding before and after the training. The results showed that FLS training significantly improved the financial literacy of participants. An R square value of 72.93% indicates the training's contribution to enhancing participants' knowledge and understanding of household financial literacy. This program effectively equips housewives with financial skills that support family economic resilience and holds the potential for replication in other community groups.